Welfare implications of fiscal reform: The case of food subsidies in India - Sonia R. Bhalotra (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper investigates the effect of a food subsidy programme in India on child malnutrition by addressing the following linked questions using household survey data that includes information on usage of the public distribution system. First, does the food subsidy induce higher expenditures on food? Second, are there gender inequalities in the distribution of food within the household, and in the gains from the food subsidy? Third, does food spending impact on child health? Is this effect similar for boys and girls and in the short and the medium term? These questions are of interest with respect to the unusually high incidence of malnutrition in India, and they are topical in the context of current and controversial reform of the public distribution system through which the food subsidy operates.
Keywords: I1; I3; O1; H4; D1; C2; 330; child malnutrition; food subsidies; poverty; welfare; health; gender; India; Nahrungsmittelsubvention; Kinder; Unterernährung; Geschlecht; Indien